The process of mediation in collective bargaining in Germany with particular focus on the role of the mediator - Baer, Christoph Richard (2014)
In Germany, when employees and employers cannot find a mutually acceptable agreement during collective bargaining themselves they can ask a third person to act as mediator. The question of interest is whether or not the person who actually assumes that position is relevant to the outcome of such mediation. And if he is relevant then what makes a mediator and thus mediation successful eventually leading to a new collective agreement to be signed and potential strikes to be prevented or terminated? The available, albeit limited literature suggests several characteristics, skills and tactical approaches to be decisive. Those include: intelligence, good comprehension and understanding, empathy, experience in leading roles, reputation, the ability to exert pressure on and having separated sessions with both parties. Based on these ideas I have conducted seven semi-structured interviews with ten interviewees talking to all participants of the mediation process: mediators, employees and employers. These account for two highly observed mediation rounds in Germany, one in the private and one in the public sector. The mediators who have been interviewed are both former prime ministers (Ministerpräsidenten) of German federal states (Bundesländer). The results obtained have mostly confirmed the existing literature. Most participants have highlighted the importance of the mediator´s reputation which is among other things used to assist the parties in graceful withdrawal. Impartiality and balance of trust were also judged to be decisive. Almost all interviewees agree that specific training in mediation is not necessary: in their views a mediator must have learned and acquired the techniques and skills required during his challenging and distinctive professional life. A mediator must be careful not to overexert the parties with his creativity or the use of typical mediation techniques as this will be observed and detected easily. He should feature intellectual and emotional skills to the same extent and does not need a specific professional background. Former top politicians are considered especially suitable for the job since they have learned to integrate and organize consensus in a flexible manner. In order to ask enlightening questions, guide and lead the whole process the mediator needs sufficient knowledge about the subject matters at hands or he should at least be able to develop such understanding. Overall, all participants agree that the mediator´s personality, conduct and skills do make a difference. Mediation relies on that third person that is the new inspiring element after the regular negotiations have failed. Mediation in collective bargaining can thus succeed or fail due to the mediator.